Beyond Technical Skills: Academic Language Proficiency and Perceived Difficulty in Technical and Vocational Institute - Shewangizaw, Gashaw (Elsya : Journal of English Language Studies, 2024)
Effective communication skills are important for vocational trainees' academic and career success. However, limited research has examined language learning difficulties specific to Ethiopian technical contexts. This study explored self-perceived English language difficulties among trainees in building construction, road construction, water construction, surveying, architectural design, wood science technology programs at the Federal Technical and Vocational Training Institute. It aimed to identify difficult language skills and determine relationships between perceived difficulties and demographic factors. A sample of 138 trainees from Civil Technology Faculty of a TVT Institute was selected through stratified random sampling. Data were collected using a questionnaire measuring perceived difficulty of reading, writing, listening and speaking skills. Semi-structured interviews were conducted with 10 purposively selected trainees. Descriptive statistics, thematic analysis and constant comparison were employed for quantitative and qualitative analyses. Quantitative findings showed academic writing skills perceived as most difficult, particularly understanding conventions. Academic listening skills like note-taking and summarizing also posed challenges. Interviews revealed unfamiliarity with genres and lack of background knowledge exacerbated difficulties. Perceptions differed by trainees' program, gender and English proficiency. Thematic analysis identified factors like anxiety, experience, and self-efficacy as influencing perceptions. The study provided a comprehensive understanding of TVT Institute trainees' academic language needs in Ethiopia. Targeted support is recommended to scaffold challenging skills based on identified individual differences and modifiable difficulties. Mainstreaming language development across the curriculum optimizes trainees' preparedness for technical careers and lifelong learning. This mixed methods exploration of language difficulty perceptions contributes to knowledge on dimensions shaping TVT Institute students' experiences. Findings inform tailored instruction and program improvements to better equip diverse learners for workplace competencies.